Potent Neutralizing Humanized Antibody With Topical Therapeutic Potential Against HPV18-Related Cervical Cancer - Huang, Bilian; Zhu, Linjing; Wei, Hongxia; Shi, Haixia; Zhang, Doudou; Yuan, Huanyun; Luan, Linlin; Zheng, Nan; Xu, Shijie; Nawaz, Waqas; Hong, Ying; Wu, Xilin; et al. (Frontiers in Immunology, 2021)
Cervical cancer caused by human papillomavirus (HPV) infections is the fourth most common cancer in women worldwide. Current prophylactic HPV vaccines have achieved promising success in preventing HPV infection. However, still 570,000 new cases were reported in 2018. The current primary treatment for the patient with cervical cancer is either surgery or chemoradiotherapy. Cervical cancer still lacks standard medical therapy. HPV18 induced cervical cancer has the worst prognosis and high mortality compared to other HPV infections. The development of HPV18 related with cervical malignancy requires the persistent infection of cervical-vaginal epithelium by HPV18 subtype, which can take years to transform the epithelium. This period of repeated infection provides a window for therapeutic intervention. Neutralizing antibodies formulated as topical agents that inhibit HP18V infection should reduce the chance of cervical malignancy. We previously demonstrated that potent neutralizing anti-sera against HPV18 infection were induced by HPV18 viral like particle (VLP) generated in mammalian cells. We, therefore, isolated two potent neutralizing antibodies, 2A12 and 8H4, from over 3810 hybridomas prepared from mice immunized with HPV18 VLP. 2A12 and 8H4 exhibited excellent potency, with 50% virus-inhibitory concentrations (IC50) of 0.4 and 0.9 ng/ml, respectively. Furthermore, 2A12 and 8H4 recognized distinct and non-overlapping quaternary epitopes and bound specifically with HPV18. Humanized 2A12 (Hu2A12) retained comparable neutralizing activity against HPV18 infection in various acidic pH settings and in hydrogel formulation with IC50 values of 0.04 to 0.77 ng/ml, indicating that Hu2A12 will be a promising candidate for clinical development as a topical vaginal biopharmaceutical agent against HPV18 infection.